Kepentingan Umum Dalam Asas Oportunitas Pada Sistem Peradilan Pidana - Badaru, Baharuddin (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to examine and analyze the criteria of public interest in the opportunity principle in the criminal justice system. This study uses a normative legal method approach by applying a statutory perspective, especially referring to Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia, the Criminal Procedure Code (KUHAP), and involving legal theory and the views of legal experts as sources of supporting material, both in the form of secondary, primary, and tertiary law. Through this research, the authors succeeded in obtaining solutions to the challenges that arose in line with the development of the opportunity principle which has undergone many changes. This change is clearly reflected in the context of the Law on the Attorney General's Office which rules out cases based on considerations of the public interest within the framework of the opportunity principle in the criminal justice system. This change can be seen from the beginning of Article 8 of Law Number 15 of 1961 up to Article 35 letter c of Law Number 16 of 2004 which relates to the Attorney General of the Republic of Indonesia. The criteria for the public interest in the opportunity principle include the interests of the state, the interests of society and personal interests. However, the interpretation of these criteria still does not provide concrete explanations and measurements, so as to produce different understandings among different groups. The ambiguity in these regulations indicates the need for regulations contained in a law to be formed by involving relevant parties who have a deep understanding of the opportunity principle. In this way, it is hoped that the process of forming regulations will include collaboration with experts and legal practitioners who have in-depth knowledge of the opportunity principle. This will help ensure that the resulting regulations are more concrete, clear, and can be interpreted consistently by various parties involved in the criminal justice system.